MAKING AN OLD CITY A PLEASANT PLACE TO STAY FOR MENEER AND MEVROUW: SOLO, 1900-1915 - . Kuntowijoyo (Humaniora, 2000)
In 1900 Solo was already a multiracial city, though the Javanese were dominating the scene . The whole population was 109,459 . out of which 1,973 were Europeans, 5,129 Chinese, 171 Arabs, 262 Other Foreign Easteners, and the rest 101,924 Javanese (RA, 1902) . Five years later in 1905 the population increased to 118,378, out of which 1,572 were Europeans, 6,532 Chinese, 337 Arabs. 413 Other Foreign Easteners, and 109,524 Javanese (RA, 1908) . The same sources showed that at these times the Javanese population of the whole Surakarta were respectively 1 .499,438 and 1,577,996, thus it was only about one fifteenth of the native lived in *!he capital city. The reverse was true to the foreigners. Numbers showed that in 1900 in the whole Surakarta there were 3,637 Europeans . 9,265 Chinese. 171 Arabs, and 262 Other Foreign Easteners : meanwhile in 1905 there were 3,335 Europeans, 10,971 Chinese, 337 Arabs . and 417 Other Foreign Easteners. These numbers meant that the Arabs and Other Foreign Easteners practically all lived in the capital city . The Dutch administration of the city divided the territory into several wijk (neighbourhood), each with its own wijkmeester (chief). After expansion, there were three wijk in 1915. First, the wijk of South-East. It was with the Pepe in the north, the Bengawan in the east, the end of the city in the South, and the street through the Pepe bridge and the Mangkunegaran palace to the south up to the southern end of the city . Second, the wijk of the North-East . It was with the northern end of the city in the north, the Bengawan in the east, the Pepe in the south, and the Pepe in the west. Third, the wO of the Westside . It was with the northern end of the city and the Pepe in the north, the Pepe and the road through the bridge of the Pepe to the south of the Mangkunegaran palace in the east, the end of 'the city in the south, and the west end of the city to the west (DNV, 3-9-1915) . The Chinese lived in their own wijk with a wijkmoester appointed by the colonial government (RA, 1906 : 272). Their kampongs were Jebres (Mesen), Kepatihan, Balapan, and houses along the streets in the Kasunanan part of the city . So did the Arabs who lived in their own wijk, Pasar Kliwon .